Lipid Metabolism Alterations in Hyperlipidemic Dogs with Biliary Tract or Endocrine Diseases - Tae-Woo Kim; Min-Hee Kang; Hee-Myung Park (Animals)
Fasting hyperlipidemia results from lipid metabolism defects associated with alterations in specific lipoprotein classes. These changes may originate from genetic predispositions or underlying metabolic disorders, including cholestasis and endocrine diseases. This retrospective study aimed to analyze variations in lipoprotein electrophoresis (LPE) profiles in hyperlipidemic dogs and investigate the associations between biliary tract diseases, endocrine disorders, and lipid metabolism. Sixty-five dogs that underwent LPE were classified into non-hyperlipidemic (NHL) and hyperlipidemic (HL) groups, with further subdivisions based on the presence of biliary tract disease, endocrine disorders, or breed predisposition (Miniature Schnauzers). Dogs in the HL group with biliary tract disease and those with underlying metabolic disorders exhibited significantly higher pre-beta fractions and cholesterol concentrations compared to the NHL group. Additionally, significant linear relationships were observed between serum gamma-glutamyl transpeptidase (GGT) levels and both pre-beta fractions and cholesterol concentrations. The Schnauzer group showed lower alpha fractions and higher triglyceride and cholesterol levels than the NHL group. These findings suggest that LPE is a valuable and useful tool for detecting lipid metabolism abnormalities. Clinicians should consider the potential for altered lipid metabolism when evaluating patients with biliary tract or endocrine diseases in small animal practice.